Effect of MnSi2‐Induced Solid Solution Strengthening on Mechanical Behavior of 316L Stainless Steel Fabricated by Selective Laser Melting. Issue 9 (29th April 2021) - Li, Meng; Wu, Meiping; Lu, Peipei; Liu, Xin; Wang, Yiyao; Miao, Xiaojin
Abstract : As an emerging additive manufacturing technology, selective laser melting (SLM) can manufacture metal matrix composites with high performance. Herein, a MnSi2 compound is innovatively utilized to improve the mechanical properties of the 316L substrate. The results indicate that an appropriate mass fraction of the MnSi2 compound can promote the solid solution, leading to an increment in the surface quality, microhardness, and tensile strength of the 316L substrate. When the addition of MnSi2 is 6.0 wt%, the sample exhibits the highest microhardness and tensile strength with the value of 426 HV0.2 and 860 MPa, respectively. However, microcracks are observed and the ultimate tensile displacement is decreased synchronously; meanwhile, its fracture behavior exhibits mixed‐mode ductile fracture and brittle fracture. Overall, this study explains a novel hypothetical mechanism of solid solution reinforcement by adding a MnSi2 compound into 316L. Abstract : Herein the effect of MnSi2 compound content on the micro‐hardness and tensile strength of 316L stainless steel composites fabricated by selective laser melting is investigated. The results indicate the appropriate mass fraction of the MnSi2 compound can promote the solid solution, leading to an increment of the mechanical properties.